Geomagnetically Induced Current Model in New Zealand Across Multiple Disturbances: Validation and Extension to Non‐Monitored Transformers. Issue 2 (18th February 2022) - Mac Manus, D. H.; Rodger, C. J.; Ingham, M.; Clilverd, M. A.; Dalzell, M.; Divett, T.; Richardson, G. S.; Petersen, T.
Abstract: Geomagnetically induced currents (GICs) produced during geomagnetic disturbances pose a risk to the safe operation of electrical power networks. One route to determine the hazard of large and extreme geomagnetic disturbances to national electrical networks is a validated model to predict GIC across the entire network. In this study, we improve upon an earlier model for New Zealand, expanding the approach to cover transformers nationwide by making use of multiple storms to develop national scaling factors. We exploit GIC observations which have been made and archived by Transpower New Zealand Ltd, the national grid operator. For some transformers the GIC observations span nearly 2 decades, while for others only a few years. GICs can vary wildly between transformers, particularly due to differences in the electrical network characteristics, transformer properties, and ground conductivity. Modeling these individual transformers is required if an accurate representation of the GIC distribution throughout the network is to be produced. Here we model the GIC during 25 disturbed periods, ranging from large geomagnetic storms to weakly active periods. We adopt the approach of scaling model output using observed GIC power spectra, finding that it improves the correlations between the maximum model and observed GIC by between 10% and 40% depending on the transformer. The modeled GIC at the 73 transformers which have measured GIC are analyzed to create local and national scaling curves. These are used to allow modeling for transformers without in‐situ GIC. We present approaches to utilize this technique for future storms, including non‐monitored transformers. Plain Language Summary: Space Weather events can affect the safe operation of electrical power networks. Specialized instruments have been installed in the New Zealand electrical network to measure unwanted direct current (DC) currents at transformers and monitor this risk. The measurements from these instruments are compared against a model, which tries to predict these currents at all electrical transformers across the entire network. We compare the measured and modeled current across multiple events to help validate the model at sites that are not directly measured, as well as sites which have measurements. Due to differences in the electrical network characteristics, transformer properties, and ground conductivity, the DC current through any two transformers can vary dramatically. The events we model cover large and small space weather periods. Using the measured currents for these events, we can scale the model output to produce a more accurate representation of the DC current throughout the whole network. This is a step toward modeling the unwanted currents during extreme space weather events. Key Points: Modeling geomagnetically induced currents (GIC) in New Zealand for multiple past geomagnetic disturbances shows good agreement with measurements at South Island transformers Scaling the modeled GIC in the frequency domain using past GIC measurements produces more accurate modeling results Averaged frequency scaling can be applied to transformers without measurements enhancing the models value for future extreme storm studies